PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) UNTUK SMP KELAS VIII - Oktavia, Refni - (STKIP PGRI Sumbar, 2014)
Teaching materials is one of the things that can affect the quality of learning. Teaching materials should be able to train the students learning independence, so that students can find the concept independently, and reason as well as the mindset of students can develop. The purpose of the development of LKS with Contextual Teaching and Learning approach is generating a valid and practical worksheets. This type of research is the development of research using model 4-D which consists of four phases: define (definition), design (design), develop (development), and desseminate (spread). The tests showed that the LKS has a validity of 3.01 which is included in the valid criteria. The test results showed that the practicalities of the teacher student worksheets with Contextual Teaching and Learrning approach has a level of 75% which includes the practicalities of practical criteria. While the practicalities of student test results showed that the approach LKS Contextual Teaching and Learrning (CTL) has a 97% rate of practicalities which includes very practical criteria.